ALIRAN MUTAZILAH DALAM LINTASAN SEJARAH PEMIKIRAN ISLAM - Mawardy Hatta (Jurnal Ilmiah Ilmu Ushuluddin, 2013)
One school of Kalam/Islamic theology that once flourished in antiquity was Mu'tazila flow. Flow pattern known as rational and liberal thought that was growing and evolving so rapidly and peaked in the Abbasid era in particular Khalifah Al- Ma'mun because of the support and protection of the khalifah. But then, the glory and the gold period did not last long, it eventually flew into decline. It was caused by a variety of factors, most importantly; they had done violence coercion and even torture of a number of scholars in the event of al - mihnah when imposing the concept of "Al-Quran beings". The violence was bad for the flow Mu'tazila antagonizing people. They were followed also by the beginning of a new stream of traditional and more moderate, Ash'arite. This stream got a lot of sympathy among the people. The Mu'tazila flow was progressively weaker and eventually disappear from the Islamic world.